2020
DOI: 10.1097/md.0000000000022782
|View full text |Cite
|
Sign up to set email alerts
|

Conversion therapy for unresectable hepatocellular carcinoma after lenvatinib

Abstract: Introduction: Lenvatinib (LEN) is a novel potent multi-tyrosine kinase inhibitor, approved as first-line treatment for unresectable hepatocellular carcinoma (HCC). Considering its high objective response rate, LEN therapy could be expected to achieve downstaging of tumors and lead to conversion therapy with hepatectomy or ablation. However, the feasibility of conversion therapy after LEN treatment in unresectable HCC remains largely unknown. Patient concerns: Here, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 21 publications
(23 reference statements)
2
39
0
1
Order By: Relevance
“…Considering the selection of first‐line MTAs for u‐HCC, LEN might be preferable to SOR when tumor shrinkage is needed for controlling intrahepatic tumors, which are at a high risk of rupture or macrovascular invasion 26 . Moreover, LEN is expected to show a high possibility of downstaging u‐HCC with a high tumor burden, resulting in a switch to locoregional therapies such as conversion hepatectomy 27–29 . However, more studies are needed for investigating the therapeutic efficacy of conversion therapy using LEN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the selection of first‐line MTAs for u‐HCC, LEN might be preferable to SOR when tumor shrinkage is needed for controlling intrahepatic tumors, which are at a high risk of rupture or macrovascular invasion 26 . Moreover, LEN is expected to show a high possibility of downstaging u‐HCC with a high tumor burden, resulting in a switch to locoregional therapies such as conversion hepatectomy 27–29 . However, more studies are needed for investigating the therapeutic efficacy of conversion therapy using LEN.…”
Section: Discussionmentioning
confidence: 99%
“…26 Moreover, LEN is expected to show a high possibility of downstaging u-HCC with a high tumor burden, resulting in a switch to locoregional therapies such as conversion hepatectomy. [27][28][29] However, more studies are needed for investigating the therapeutic efficacy of conversion therapy using LEN.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment for high-risk patients needs to be carefully considered, and the prognosis of patients undergoing surgical treatment is worse than that of patients with systematic treatment [41]. At present, after conversion therapy is effective, surgical treatment has also achieved a good prognosis, but more researches are needed to determine whether this treatment regimen will benefit all high-risk patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports about conversion hepatectomy for advanced hepatocellular carcinoma after lenvatinib therapy [ 10 16 ]. Sato et al and Tomonari et al reported conversion hepatectomy for HCC after transarterial chemoembolization (TACE) and lenvatinib therapy [ 10 , 11 ]. Matsuki et al reported a complete pathological response in conversion hepatectomy from lenvatinib treatment for advanced hepatocellular carcinoma [ 12 ].…”
Section: Discussionmentioning
confidence: 99%